Wheat Straw Biochar Increases Potassium Concentration, Root Density, and Yield of Faba Bean in a Sandy Loam Soil. Issue 15 (22nd August 2019) - Poormansour, Samaneh; Razzaghi, Fatemeh; Sepaskhah, Ali Reza
ABSTRACT: A greenhouse experiment was conducted to study the effect of different irrigation levels (100%, 75%, and 50% of water requirement) and wheat straw biochar levels (0%, 1.25%, 2.5%, 3.75%, and 5% w/w) on faba bean yield, water productivity, root length density, and different ions concentration in soil solution, using a factorial arrangement in complete randomized design with three replications. Results showed that application of high level of biochar (5% w/w) destroyed the plants before they reached maturity. The maximum yield was obtained in 1.25% w/w biochar under full irrigation, while the maximum water productivity was obtained in 2.5% w/w biochar and 50% of water requirement. Further, the root length density in soil top layer (0–8 cm) was significantly more than those in 8–16 cm, due to holding more water content in top layer and no drainage from the pots. Sodium, potassium, calcium and magnesium ions' concentrations in soil solution were significantly increased by increasing biochar levels; however, the rate of increase in potassium was higher than other ions due to high potassium concentration in biochar in comparison with the soil. In conclusion, application of biochar in the level of 1.25% w/w is suggested as a suitable agent to decrease water consumption and improving the crop performance.